Integrated package design: an interdisciplinary approach to package design that benefits consumer experience and brand perception. (10th November 2017) - Timney, Todd; Chamberlain, Peter
ABSTRACT: It is perplexing that Package Design has traditionally been taught as a course isolated in either Graphic or Industrial Design programs. To develop a truly unified brand narrative, package design necessitates an interdisciplinary, human-centered, and collaborative approach, which expands on the knowledge of each discipline and reaches into other areas of expertise. Communicating a brand message extends beyond the information and visual content applied to a package. The package's physical structure, materials, finishes, and interactions can also strongly influence the consumer's experience and subsequent perception of the brand. As a result, the effective communication of a brand's message requires a symbiotic relationship between the languages of two- and three-dimensional form. This paper presents case studies of successful integrated package design projects produced through an interdisciplinary studio course with 30 undergraduate design students from Graphic Communication Design and Industrial Design. The experience challenged students and professors to negotiate the intersection between disciplines while clarifying their own areas of expertise. Industrial Design students applied their knowhow of materiality and form development using digital 3D software to support the structural packaging dimension of the studio, while Graphic Communication Design students shared their informed perspective on brand messaging and 2-dimensional communication. This paper reflects on innovative new methods employed in the studio, the lessons learned, and the impact on future interdisciplinary collaborations in Package Design. GRAPHICAL ABSTRACT: